CCDC40 mutation as a cause of primary ciliary dyskinesia: a case report and review of literature. (3rd March 2015) - Sui, Weiguo; Hou, Xianliang; Che, Wenti; Ou, Minglin; Sun, Guoping; Huang, Shengxing; Liu, Fuhua; Chen, Peng; Wei, Xiaolian; Dai, Yong
Abstract: Background and Aims: Primary ciliary dyskinesia (PCD) is a rare, genetically heterogeneous disorder. Genetic defects affecting motility of cilia and flagella cause chronic destructive airway disease, situs inversus and, frequently, male infertility in PCD. To date, although several genes have been implicated in PCD, the genetic bases of most cases of PCD remain elusive. Methods: By applying a whole‐exome sequencing strategy, we reported a case of PCD carrying a novel mutant alleles in CCDC40 gene, and did literature review. Results: A 36‐year‐old nonsmoking Chinese man suffered from chronic cough since childhood and an 8‐year history of primary infertility. Lung biopsy showed respiratory bronchiolitis. Chest images showed bronchiectasis and situs inversus. Semen analysis showed high sperm counts and poor sperm motility. Transmission electron microscopy (TEM) of cilia cross‐sections showed ultrastructural defects, including inner dynein arms (IDA) defect and axonemal disorganization. To identify gene mutations that cause PCD, we performed exome sequencing to analyze genome of this patient, and discovered a previously uncharacterized mutant alleles (NM_001243342.1:c.2609G>A; p. R870H) in CCDC40 gene. In addition, we summarize the PCD disease‐causing genes and CCDC40 mutant sites based on current literature. Conclusions: We identified a novel mutant alleles in CCDC40 gene, which altered the protein sequence and resulted in the ultrastructural defects in the microtubule structure of cilia. Thereby, these defects lead to the patient with bronchiectasis, bronchiolitis and infertility.